A bibliometric analysis of cancer research funders and collaborators in Kenya: 2007–2017. (September 2022) - Vargas, Jasmin S.; Livinski, Alicia A.; Karagu, Alfred; Cira, Mishka K.; Maina, Martha; Lu, Ya-Ling; Joseph, Anyona O.
Abstract: Aim: Cancer research is essential to the development and implementation of effective control strategies and interventions. In Kenya, cancer is the third leading cause of death. Country specific research conducted by local and international investigators can inform a national plan to address local needs across the cancer care continuum. This analysis aims to provide information about the trends and types of cancer research collaborations, funding, and outputs from 2007 to 2017, to understand gaps and opportunities to strengthen Kenya-led cancer research capacity. Methods: This analysis included 243 studies from a previously published phase 1 scoping review of oncology research conducted and published in Kenya from 2007 to 2017. The citation metadata was drawn from the Web of Science and PubMed and normalized in Microsoft Excel. Using Sci2, a series of bibliometric network analyses were conducted to identify funding patterns, collaborations between authors and institutions, and the types of cancer research conducted in Kenya. Gephi and Excel provided descriptive analyses and graphs of the network. The analyses are categorized into three themes: article production, collaboration, and research topics. Results: The bibliometric analysis found 5 US-based government agencies are funding cancer research in Kenya. Kenya-Kenya institutional collaborations were most common, and half of authors with the most co-authored publications were from Kenya. The publication trend showed a gradual increase from 2011 to 2014 with a subsequent drop through 2017. Conclusion and policy summary statement: This study identifies the funders and most often published Kenyan authors and Kenyan-based institutions publishing oncology research in Kenya. It also identifies future areas to focus research and the importance of continuing to build the writing and publishing capacity on oncology research by Kenyans. Highlights: From 2007–2017, United States government agencies funded the majority of published cancer research conducted in Kenya. Partnerships between Kenya-Kenya and Kenya-US institutions were the predominant institutional collaborations identified. Kenya-based authors represented half of the most prolific authors during this period of time.